2020
DOI: 10.18231/j.sujhs.2019.022
|View full text |Cite
|
Sign up to set email alerts
|

To study the epidemiology and clinical profile of adult patients with acute abdominal pain attending tertiary care hospital

Abstract: Introduction: Acute abdomen is a very common problem in emergency department. Aims and Objectives: This study aims to find out the clinical and epidemiology profile of acute abdominal pain among patients attending emergency department of Santosh Medical College Ghaziabad. Materials and Methods: A tertiary care hospital based, cross-sectional study was conducted from January 2018-April 2019 2018, among patients presenting with acute abdominal pain to Santosh Medical College Ghaziabad, India. Data was entered on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
1
1
2
Order By: Relevance
“…Our findings indicated that AAP constituted 5.6% of ED visits. This rate is lower than those reported in the studies from Tanzania (8.5%), Nigeria (9.6%), India (16.66%), and Kenya (16.7%) (16)(17)(18)(19). However, an Italian study reported a rate of 5.8%, close to the rate we found in our cohort (20).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Our findings indicated that AAP constituted 5.6% of ED visits. This rate is lower than those reported in the studies from Tanzania (8.5%), Nigeria (9.6%), India (16.66%), and Kenya (16.7%) (16)(17)(18)(19). However, an Italian study reported a rate of 5.8%, close to the rate we found in our cohort (20).…”
Section: Discussioncontrasting
confidence: 69%
“…The gender distribution in our study is different from other reports. 15,16,18,20,21 For example, a national population-based cohort study from Australia found that the number of female patients (63.3%) tended to be higher than that of males (15) (16,18,21). In addition, a national population-based cohort study from Italia also detected that the rate of female patients (52%) tended to be higher than that of males (20).…”
Section: Discussionmentioning
confidence: 99%
“…O diagnóstico e manejo clínico do abdome agudo inflamatório depende da sua etiologia. As principais etiologias incluem a colecistite aguda (44% dos casos), apendicite aguda (25%), diverticulite aguda (9%) e pancreatite aguda (5%) (AGARWAL et al, 2019).…”
Section: Tipos De Abdome Agudounclassified
“…Faculdade Morgana Potrich (FAMP), Mineiros -GO 2. Universidade do Extremo Sul Catarinense (UNESC), Criciúma -SC.…”
unclassified